2020
DOI: 10.1302/2633-1462.111.bjo-2020-0107.r1
|View full text |Cite
|
Sign up to set email alerts
|

How useful are virtual fracture clinics?

Abstract: Background Due to the overwhelming demand for trauma services, resulting from increasing emergency department attendances over the past decade, virtual fracture clinics (VFCs) have become the fashion to keep up with the demand and help comply with the BOA Standards for Trauma and Orthopaedics (BOAST) guidelines. In this article, we perform a systematic review asking, “How useful are VFCs?”, and what injuries and conditions can be treated safely and effectively, to help decrease patient face to face consultatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 53 publications
6
20
1
Order By: Relevance
“…This will allow physicians to spend more time on patients with more complex injuries, teaching, training, or improving standards of care. Frequently, studies, including several systematic reviews performed recently [32][33][34], report on the effects of the VFC model as a whole. This model includes both DD of simple stable musculoskeletal injuries, as well as a daily VFC review, consequently including more complex injuries that require follow-up (Fig.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…This will allow physicians to spend more time on patients with more complex injuries, teaching, training, or improving standards of care. Frequently, studies, including several systematic reviews performed recently [32][33][34], report on the effects of the VFC model as a whole. This model includes both DD of simple stable musculoskeletal injuries, as well as a daily VFC review, consequently including more complex injuries that require follow-up (Fig.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…A recent systematic review confirmed the safety, efficacy and cost-effectiveness of the virtual fracture clinic model within the broader provision of trauma services. 19 However, it was notable that this review of 21 articles contained a single series of 253 children managed by a dedicated paediatric virtual fracture clinic pathway. 6 Other reports describe results from isolated protocols to manage individual childhood injuries 20 or describe an iterative processes to implement a virtual fracture clinic within the setting of district general hospital.…”
Section: Discussionmentioning
confidence: 99%
“…2 , 9 , 12 However, there is variation in practice across the UK, including the grade of staff making management decisions, provision of verbal and written information, and local treatment protocols for specific injuries. 12 Prior to the pandemic, several studies have reported good acceptability of the VFC model in their local centres in the management of specific injuries, such as fifth metacarpal fractures, 3 , 21 fifth metatarsal fractures, 3 , 22 clavicle fractures, 23 mallet finger injuries, 24 and ankle fractures. 25 However, a high index of suspicion and expertise may be required in the management of other types of injuries with lower prevalence but higher morbidity where radiographs may be misinterpreted, to avoid adverse outcomes and complications.…”
Section: Discussionmentioning
confidence: 99%
“… 25 However, a high index of suspicion and expertise may be required in the management of other types of injuries with lower prevalence but higher morbidity where radiographs may be misinterpreted, to avoid adverse outcomes and complications. 12 , 15 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation